2022
DOI: 10.3390/foods11223627
|View full text |Cite
|
Sign up to set email alerts
|

Production of Bacterial Cellulose in the Medium with Yeasts Pre-Fermented Coconut Water or with Addition of Selected Amino Acids

Abstract: The uncontrolled natural pre-fermentation process of coconut water represents great hidden safety hazards, unstable production, and impact on the quality of nata de coco–the trade name of bacterial cellulose (BC) in food industry. In this study, BC production from Komagataeibacter nataicola Q2 was conducted in the media of coconut water (50%, v/v) pre-fermented by 11 coconut-sourced yeast strains in static. Results suggested that coconut water pre-fermented by different yeast strains had varied effects on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“… Son et al (2003) found that the addition of tyrosine, valine, methionine, isoleucine, and glycine significantly inhibited BC production in Acetobacter sp. In our recently published study ( Lin et al, 2022 ), we demonstrated that the addition of serine significantly reduces BC production in natural fermented coconut water, whereas the addition of aspartic acid, glutamic acid, methionine, and isoleucine promotes BC production. These findings suggest that amino acids have a significant impact on BC production, but the effects may differ across bacterial strains.…”
Section: Discussionmentioning
confidence: 72%
“… Son et al (2003) found that the addition of tyrosine, valine, methionine, isoleucine, and glycine significantly inhibited BC production in Acetobacter sp. In our recently published study ( Lin et al, 2022 ), we demonstrated that the addition of serine significantly reduces BC production in natural fermented coconut water, whereas the addition of aspartic acid, glutamic acid, methionine, and isoleucine promotes BC production. These findings suggest that amino acids have a significant impact on BC production, but the effects may differ across bacterial strains.…”
Section: Discussionmentioning
confidence: 72%
“…The Special Issue focuses on the application of microorganisms in fermented foods, and it comprises four original papers [6][7][8][9] that address the third topic. In the first study [6], conducted by Feng et al, the production of baijiu using four strains of actinomycetes (Streptomyces violascens SPQ1, S. sampsonii SPS1, S. thermophilus SPG1, and S. griseus SPH1) was investigated.…”
mentioning
confidence: 99%
“…The second study conducted by Lin et al [7] sheds light on the impact of prefermentation, using different yeast strains, on bacterial cellulose (BC) production in coconut water media. The findings emphasize the variability in BC yield when utilizing prefermented coconut water compared to fresh coconut water, with the pre-fermentation by Saccharomyces cerevisiae SC7 resulting in a remarkable 165% increase in BC yield.…”
mentioning
confidence: 99%